Age-Inclusive Transit Environments: An Exploration of Public Transportation Systems for Elderly - Zakaria, Aina Mardia; Kamaluddin, Noor Azreena; Hashim, Wardati; D’Agostino, Carmelo (Environment-Behaviour Proceedings Journal, 2024)
The rising elderly population and rapid urban development have given rise to many interconnected challenges demanding transformative changes in the living environments to facilitate improved mobility and accessibility for the elderly. These issues encompass insufficient accessibility and infrastructure that do not cater to the needs of the elderly. This research explores the public transportation facilities in urban areas, encompassing infrastructure, services, and amenities that are accessible to the public and designed to facilitate community mobility and to identify the current facilities in public transportation and assess how effective and accessible they are for the elderly population.